Interconnected alchemy: an apparatus for alchemical algorithms - De Roure, David; Wilcox, Pip; Chamberlain, Alan (2017)
The trope of the fraudulent or occult alchemist, prevalent since the mediaeval period of alchemy’s introduction into European thought, belies the endeavour of practitioners from ancient Egypt onwards. Alchemists used observation, experimentation, and drew conclusions to understand the world around them. Notions of interconnectedness, harmoniousness and codification pervade the alchemical pursuit—and alchemy interconnects literature, art, mathematics, and music....One of our tools is "numbers into notes", a web app for algorithmic composition based on early mathematics, in which the role of the human is to parameterize the algorithm and map number ranges to musical notes